ANALYSIS OF CLASS V TEACHER'S LEADERSHIP STYLE AMONG STUDENTS OF SDN 060877 MEDAN PERJUANGAN - Hatmi, Edizal; Siregar, Hanif Luthfi (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Kupang, 2024)
This research is conducted to discover the leadership style of grade V teachers at SDN 060877 Medan Perjuangan and its influence over the students. The approach used in the study is a qualitative descriptive method where data were collected from the sample of ten classroom teachers through semi-structured interviews, focus group discussions, and documentation. The results of this research have shown that the greater number of teachers applied such a style of leadership, which enhances students' desire and interest to learn, to be more precise, to learn in this autocratic leadership style. The students' motivation was found to fall and during this laissez faire–style some of them were found confused for not having proper guidance. These findings agree with the theory of educational leadership theories, which insist that students be active in a process for better results. The present study suggests that educators practice more of the participative leadership style and take training for leadership development to develop leadership. So as to foster a more participatory and effective classroom atmosphere which enhances students' disposition and performance.